THE ROLE OF MOLECULAR-GENETIC MARKERS IN THE DETERMINING OF SURGICAL TREATMENT OF STOMACH CANCER PATIENTS - I. I. Bykov (Сеченовский вестник)
This article deals with the problem of determining of surgical treatment of the stomach cancer patients.